Effect of habitat heterogeneity in the composition and distribution of Chironomidae (Diptera) assemblage in different microhabitats of preserved streams in the Brazilian Atlantic Forest - Fernanda de Almeida Gurski; Gisele Daiane Pinha; Yara Moretto; Alice Michiyo Takeda; Norma Catarina Bueno (Acta Limnologica Brasiliensia, 2014)
AIM: This study aimed at to evaluate the influence of habitat heterogeneity on the attributes of richness, abundance, diversity and equitability of Chironomidae assemblage and also the biological differences in faunistic composition related to each microhabitat. METHODS: The sampling was performed in summer (February) and winter (August) 2010, with Surber sampler, in three headwaters streams at Atlantic Forest, in southern Brazil. RESULTS: In the total 6,429 Chironomidae larvae were identified and classified into 96 taxa belonging to Chironominae, Tanypodinae and Ortocladiinae subfamilies. Among the microhabitats, the highest richness was observed in the deposits of litter, and the highest number of exclusive species took place in the pool regions. CONCLUSIONS: Thus, the composition and structure of the Chironomidae assemblage are directly related to the availability and heterogeneity of habitats in streams.